2021
DOI: 10.1186/s11671-021-03528-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anisotropy and In-Plane Grain Boundary in Cu/Pd Multilayered Films with Cube-on-Cube and Twinned Interface

Abstract: In crystalline materials, grain boundary and anisotropy of crystal structure affect their mechanical properties. The effects of interfacial structure on the mechanical properties may be diverse when the multilayer film is loaded along different directions. In this work, we performed a series of molecular dynamics simulations of the tension of in-plane single and polycrystalline Cu/Pd multilayered films with cube-on-cube (COC) and twinned interfaces to explore the effects of the interfacial structure, loading d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The formation and propagation of cracks would reduce the load-bearing capacity of PGr. With the increase of strain, dislocations are emitted from the crack at the interface between PGr and Cu due to stress concentration, resulting in the rapid decrease of stress. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation and propagation of cracks would reduce the load-bearing capacity of PGr. With the increase of strain, dislocations are emitted from the crack at the interface between PGr and Cu due to stress concentration, resulting in the rapid decrease of stress. , …”
Section: Resultsmentioning
confidence: 99%
“…It has been recognized that the strengthening of a Gr-metal composite mainly comes from the high load-bearing capacity of Gr and the obstruction to the propagation of dislocations by the interface between Gr and metals. ,, Molecular dynamics (MD) simulations are a powerful means to investigate the mechanical behavior of composites because they can visually reveal the underlying atomic-level processes of deformation. Liu et al studied the interfacial enhancement effect of nanolaminated Gr/Cu composites under shear and found that the interfacial constraint effect could improve the shear strength and toughness . Peng et al simulated using MD the responses of a single-crystalline graphene/Cu (SC Gr/Cu) multilayer under uniaxial tension and reported that the strengthening is related to the chirality of Gr .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics methods, as a numerical method for detailed microscopic modeling at the molecular scale, have recently been widely applied to the research of mechanical properties of different types of crystalline materials [15][16][17]. Tang and Horstemeyer et al studied the fatigue mechanical behavior of single magnesium crystals with different orientations using the MD method [18], and then, reviewed atomic simulation studies of microscopic crack extension in nickel and cooper [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rapid development of experimental technology, it is still very challenging to study the evolution of SFTs under shear stress in different directions through experiments. Molecular dynamics (MD) simulations is an effective means to investigate the formation and evolution of microstructures under irradiation (Aidhy et al, 2015;Drouet et al, 2016;Dai et al, 2017;Zhu et al, 2017;Leino et al, 2018;Ke et al, 2019) and various mechanical loading (Weng et al, 2020;Chen et al, 2021;Weng et al, 2021), and the evolution of SFTs (Wu et al, 2018b;Wu et al, 2018c;Zhang et al, 2018;Chen et al, 2020). To study the formation and aggregation of vacancies using MD simulation of irradiation requires a long time and a lot of computing resources.…”
Section: Introductionmentioning
confidence: 99%